2000
DOI: 10.1128/aem.66.4.1274-1279.2000
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Filamentation of Salmonella enterica Serovar Enteritidis PT4 and Salmonella enterica Serovar Typhimurium DT104 at Low Water Activity

Abstract: In this study we investigated the long-term survival of and morphological changes in Salmonella strains at low water activity (a w ). Salmonella enterica serovar Enteritidis PT4 and Salmonella enterica serovar Typhimurium DT104 survived at low a w for long periods, but minimum humectant concentrations of 8% NaCl (a w , 0.95), 96% sucrose (a w , 0.94), and 32% glycerol (a w , 0.92) were bactericidal under most conditions. Salmonella rpoS mutants were usually more sensitive to bactericidal levels of NaCl, sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 38 publications
7
112
1
1
Order By: Relevance
“…They found that filament formation with increased filament length became apparent in 5% sodium chloride and 7% potassium chloride (Zarei et al, 2012). These findings were also observed in Salmonella at low water activity and low temperature (Mattick et al, 2000(Mattick et al, , 2003.…”
Section: Resistance To Bacteriocinssupporting
confidence: 65%
“…They found that filament formation with increased filament length became apparent in 5% sodium chloride and 7% potassium chloride (Zarei et al, 2012). These findings were also observed in Salmonella at low water activity and low temperature (Mattick et al, 2000(Mattick et al, , 2003.…”
Section: Resistance To Bacteriocinssupporting
confidence: 65%
“…It is interesting to speculate that extracytoplasmic stress response functions regulated by s E would be required for survival of Salmonella in other microenvironments where conditions of osmotic shock may be experienced (Mattick et al, 2000). These might include bile salts and foods with low a w properties, for example.…”
Section: Resultsmentioning
confidence: 99%
“…NaCl is one of the most important agents in food preservation, known since ancient times to be a potent microbial inhibitor. More recent studies show that NaCl and osmotic stress affect virulence factor expression in numerous bacterial species, such as Salmonella spp., Escherichia coli, and Helicobacter pylori (19,33,37).…”
mentioning
confidence: 99%